Current perspectives on neuroimaging techniques used to identify stroke mimics in clinical practice. (4th May 2021) - El-Wahsh, Shadi; Dunkerton, Sophie; Ang, Timothy; Winters, Hugh Stephen; Delcourt, Candice
ABSTRACT: Introduction: Urgent clinical assessment and brain imaging are essential for differentiating stroke mimics from stroke and to avoid unnecessary initiation of reperfusion and other therapies in stroke mimic patients. Areas covered: In this article, the authors will review acute stroke imaging and then the imaging patterns of the most common stroke mimics. The authors have focused our review on brain CT scan, and more specifically CT perfusion, as this is the most commonly available and emerging tool in emergency settings. The authors also provide information on acute brain MRI and MR perfusion. Expert opinion: Imaging can contribute to the detection and diagnosis of acute stroke mimics. Knowledge of imaging findings in different stroke mimics can help distinguish these from patients with stroke who require timely reperfusion therapy. CT and MRI perfusion and diffusion-weighted imaging (DWI) MRI are useful imaging modalities for the assessment of acute stroke patients as they provide more accurate information than plain CT scan. Some of these modalities should be available in the emergency setting. The authors recommended CT perfusion as a useful tool for stroke management and differentiation with stroke mimics.